Advanced Biofuels and Bioproducts - Lee, James W. (Springer New York : Imprint: Springer, 2013)
Designed as a text not only for students and researchers, but anyone interested in green technology, Advanced Biofuels and Bioproducts offers the reader a vast overview of the state-of-the-art in renewable energies.  The typical chapter sets out to explain the fundamentals of a new technology as well as providing its context in the greater field. With contributions from nearly 100 leading researchers across the globe, the text serves as an important and timely look into this rapidly expanding field. The 40 chapters that comprise Advanced Biofuels and Bioproducts are handily organized into the following 8 sections: ·         Introduction and Brazil's biofuel success ·         Smokeless biomass pyrolysis for advanced biofuels production and global biochar carbon sequestration ·         Cellulosic Biofuels ·         Photobiological production of advanced biofuels with synthetic biology ·         Lipids-based biodiesels ·         Life-cycle energy and economics analysis ·         High-value algal products and biomethane ·         Electrofuels.